Colloids in Drug Delivery. - Fanun, Monzer (Surfactant Science, 150, 2010)
With significant applications in drug delivery and formulation science, colloids offer the same advantages of typical materials used for release but can be tailored to specific bulk material properties such as release profiles. This book presents the various findings on the application of colloidal properties in drug delivery systems.